Reporting the Covid-19 Pandemic: Trauma on Our Own Doorstep. Issue 6 (3rd July 2022) - Jukes, Stephen; Fowler-Watt, Karen; Rees, Gavin
Abstract: The political and media rhetoric of the pandemic is that of conflict and a call to arms in face of a hidden enemy. But this is not a distant war where journalists are parachuted in to report on the action for a few weeks and then fly home. It is on our own doorstep. Many of those covering the global crisis do not correspond to the popular image of hardened conflict reporters and may have little experience in dealing with distressing stories of death, grief and mourning. How are journalists coping with the everyday diet of trauma when the corona frontline may be affecting their families, friends and colleagues? this article explores these issues through narrative interviews with UK-based journalists covering the pandemic for broadcast, print and digital media. It seeks to capture their "emotional labour" and explore possible differences in their practice and the coping strategies they employ. The paper locates this discussion within the context of an industry that has paid relatively little heed to these issues and considers what long-term implications the coronavirus may have for the next generation of digital journalists.